2014
DOI: 10.1089/gtmb.2014.0098
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNP (-G1082A)IL-10with Increase in Severity of Periportal Fibrosis in Schistosomiasis, in the Northeast of Brazil

Abstract: Interleukin 10 (IL-10) is an important anti-inflammatory cytokine that modulates severe periportal fibrosis (PPF). We hypothesized that genetic polymorphisms (-G1082A/-C819T/-C592A) of the IL-10 gene and classic factors (age, sex, alcohol, exposure, and specific treatment) are associated with the severity of PPF and that these polymorphisms influence IL-10 expression. In this cross-sectional study, we genotyped these polymorphisms within the IL-10 gene in 203 Brazilian subjects infected with Schistosoma manson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…A study investigated the association of the three IL-10 promoter variants -1082G/ A, -819C/T and -592C/A with the severity of periportal fibrosis in schistosomiasis. The results showed that the -1082A/G SNP and haplotypes ACC, GTA and ATA were associated with fibrosis severity [29]. Minor alleles of the three promoter SNPs were found associated with total IgE levels and S. mansoni infection intensity in a schistosomiasis-endemic area in Brazil [30].…”
Section: Discussionmentioning
confidence: 97%
“…A study investigated the association of the three IL-10 promoter variants -1082G/ A, -819C/T and -592C/A with the severity of periportal fibrosis in schistosomiasis. The results showed that the -1082A/G SNP and haplotypes ACC, GTA and ATA were associated with fibrosis severity [29]. Minor alleles of the three promoter SNPs were found associated with total IgE levels and S. mansoni infection intensity in a schistosomiasis-endemic area in Brazil [30].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, -G1082A/-C819T/-C592A IL-10 polymorphisms and their respective serum concentrations determined for these patients (9) . The present cohort study included 119 patients infected with S. mansoni who were recruited during 2012-2013 and followed-up retrospectively for 2 years after specifi c treatment for S. mansoni to estimate the probability of PPF regression.…”
mentioning
confidence: 93%
“…In the previous study (9) with 203 patients, polymorphisms -G1082A/-C819T/-C592A IL-10 in the promoter region of the IL-10 gene were determined alongside their respective serum concentrations. Of the 203 patients in this previous study, the current study excluded 12 who had image pattern A (without PPF) in the fi rst abdominal ultrasound, 66 who did not have a follow-up of 2 years after the fi rst specifi c treatment for S. mansoni, and 6 for whom the genotype frequencies for regions (-C819T/-C592A) of the IL-10 gene were not determined.…”
mentioning
confidence: 99%
See 2 more Smart Citations